Cutaneous Adverse Reactions to Highly Antiretroviral Therapy in HIV-Positive Patients - G. Pistone; A. Pistone; D. Sorbello; E. Viviano; M.R. Bongiorno (Karger Publishers, 2013)
Adverse drug reactions to highly antiretroviral therapy (HAART) are major obstacles in its success. Although overall mortality from HIV has dramatically declined owing to HAART, these antiretroviral regimens have been associated with a wide spectrum of severe cutaneous reactions. The severity of cutaneous adverse reactions varies greatly, and some may be difficult to manage. To optimize adherence and efficacy of antiretroviral treatment, clinicians must focus on preventing adverse effects whenever possible, and distinguish those that are self-limited from those that are potentially serious. This paper presents the case of a serious cutaneous adverse reaction to Atripla in a HIV-positive 50-year-old Caucasian woman.